Reduced BMP signaling results in hindlimb fusion with lethal pelvic/urogenital organ aplasia: a new mouse model of sirenomelia. - Kentaro Suzuki; Yasuha Adachi; Tomokazu Numata; Shoko Nakada; Motoko Yanagita; Naomi Nakagata; Sylvia M Evans; Daniel Graf; Aris Economides; Ryuma Haraguchi; Anne M Moon; Gen Yamada (PLoS ONE, 2012)
Sirenomelia, also known as mermaid syndrome, is a developmental malformation of the caudal body characterized by leg fusion and associated anomalies of pelvic/urogenital organs including bladder, kidney, rectum and external genitalia. Most affected infants are stillborn, and the few born alive rarely survive beyond the neonatal period. Despite the many clinical studies of sirenomelia in humans, little is known about the pathogenic developmental mechanisms that cause the complex array of phenotypes observed. Here, we provide new evidences that reduced BMP (Bone Morphogenetic Protein) signaling disrupts caudal body formation in mice and phenocopies sirenomelia. Bmp4 is strongly expressed in the developing caudal body structures including the peri-cloacal region and hindlimb field. In order to address the function of Bmp4 in caudal body formation, we utilized a conditional Bmp4 mouse allele (Bmp4(flox/flox)) and the Isl1 (Islet1)-Cre mouse line. Isl1-Cre is expressed in the peri-cloacal region and the developing hindimb field. Isl1Cre;Bmp4(flox/flox) conditional mutant mice displayed sirenomelia phenotypes including hindlimb fusion and pelvic/urogenital organ dysgenesis. Genetic lineage analyses indicate that Isl1-expressing cells contribute to both the aPCM (anterior Peri-Cloacal Mesenchyme) and the hindlimb bud. We show Bmp4 is essential for the aPCM formation independently with Shh signaling. Furthermore, we show Bmp4 is a major BMP ligand for caudal body formation as shown by compound genetic analyses of Bmp4 and Bmp7. Taken together, this study reveals coordinated development of caudal body structures including pelvic/urogenital organs and hindlimb orchestrated by BMP signaling in Isl1-expressing cells. Our study offers new insights into the pathogenesis of sirenomelia.